Migration from Zambia : Ensuring Temporariness through Cooperation - Amin, Mohammad (World Bank, Washington, DC, 2012)
The paper analyzes migration from Zambia in order to understand how migration policy can support development in the least developed countries. Overall emigration from Zambia is not high by regional standards, but the pattern of migration is skewed toward the skilled and away from the unskilled. A development-friendly approach to migration for Zambia would strive to ensure the temporariness of both types of movement. First, industrial countries may be willing to accept a higher level of unskilled immigration if they could be certain that it is temporary. Second, any adverse effects of brain drain would be greatly alleviated if skilled emigration is temporary. The problem is that host countries cannot unilaterally ensure temporariness of unskilled migration because repatriation cannot be accomplished without the help of source countries like Zambia, and source countries today have little incentive to facilitate the return of the unskilled. At the same time, source countries like Zambia cannot unilaterally ensure temporariness of the skilled because repatriation cannot be accomplished without the help of the host countries, and host countries currently have little incentive to send back the skilled. So, there is a strong case and considerable scope for cooperation between source countries like Zambia and destination countries in the design and implementation of migration policy so that unskilled migration becomes feasible and skilled migration takes a more desirable form.